Pengkondisian dan Konflik Ibu Rumah Tangga dalam Novel Out Karya Kirino Natsuo - Ulan Sari, Ni Luh; Oeinada, I Gede; Laksmita Sari, Ida Ayu (Humanis, 2016)
This research is aimed to find out the housewife conditioning and conflict in OUT novel by Kirino Natsuo. The data were analyzed using descriptive analysis method. Then the results of the analysis is served by using informal method. This research used the theory from Roekhan (in Endraswara, 2008), Skinner (in Feist and Feist, 2013) and Stanton (in Nurgiyantoro, 2013). The conclusion from this research is conditioning experienced by the four housewives in OUT novel is operant conditioning with negative reinforcement . The results behavior of the conditioning received is hatred, avoidance, depressed, and feel life is not interesting. Meanwhile conflict found is an internal conflict and external conflict. Internal conflict develop within those housewives themselves. External conflict that was found was a conflict in the family and conflict among the four housewives.